Problematika Pembagian Harta Warisan Dalam Tradisi “Sangkolan” Pada Masyarakat Madura Perantauan : ( Studi Kasus Di Desa Sumberbulus Kecamatan Ledokombo Kabupaten Jember ) - Suparjo Adi Suwarno (ASA, 2021)
Life in indigenous peoples is very closely related to the system of kinship and kinship. Thus, not closingthe possibility of causing problems related to personal interests such as the issue of the division of inheritance land, which often causes disputes within the family environment. Indigenous peoples are regular and permanent community units whose members are not only bound to a certain residence or area. The division of inheritance using the customary law system is not without problems. From the data collected by researchers, inheritance dispute cases at the Jember Regency Religious Court show that inheritance disputes are still the most common cases being tried. In this study, the researcher intends to unravel and find the root of the problem and provide solutions to problems that are often faced by people who still use sangkolan customary law. This study reveals various probelimatika that occur in the practice of the "sangkolan" tradition which has a bad impact on social relations. With this study, researchers found various problems that needed to be resolved either through the media or through deliberation.